Estimating the impact of climate change on agricultural production: Accounting for technology heterogeneity across countries - Andreas Exenberger; Andreas Pondorfer; Maik H. Wolters (Kiel Institute for the World Economy (IfW), 2014)
We estimate the impact of climate change on agricultural production in a panel of 127 countries from 1961 to 2002. In contrast to the existing literature we account for cross-sectional dependence and technology heterogeneity. We find no significant impact of climate change on agricultural production in high income countries, but significant adverse effects in middle and low income countries. These adverse effects include a moderate negative impact of increases in temperature on agricultural output and for low income countries also negative effects of reductions in precipitation and of increases in the frequency of droughts. The latter two effects are particularly strong in Sub-Sahara Africa where low-tech rain-fed agriculture with very limited climate change adjustment capacities dominates. Thus, our findings reinforce the importance of proper adaptation strategies to climate change considering heterogeneous production technologies across countries.
Keywords: C33; N50; O13; Q54; 330; agricultural production; climate change; panel data; cross-sectional dependence; parameter heterogeneity; common correlated effects estimator